PROFESI AKUNTAN : AKAHKAH HILANG DI ERA DIGITAL 4.0? - isnawati isnawati Isnawati; Isnawati Isnawati; lukman Effendy; eni indriani (Jurnal Penelitian Akuntansi (JPA), 2021)
The results of research from McKinsey in 2016 that the impact of digital technology the 4.0 industrial revolution in the next five (5) years there will be 52.6 million types of jobs that will disappear from the earth. And one of the professions is the accounting profession. And the fact is some of the accounting profession's work has begun to be taken away, replaced by technology. This shows automatic journaling, sorftware in the field of accounting has been sold in the community, so that simple accounting jobs do not need an accountant with a college degree. This situation raises the question whether the entire accounting profession is responsible? This study used a literature approach. Several viewpoints and research results state that the accounting profession will be replaced by robots, especially accountants and auditors. However, this profession is still relevant to the presence of the 4.0 industrial revolution era if accountants can make adjustments to technology, especially the Accounting Information System, must be able to answer the challenges in the era of the industrial revolution 4.0. especially accountants must be able to prepare themselves are able to own and improve their competence, so the profession is not taken over by other professions.